(untitled) (Ameghiniana, 2021)
We present here the first record of a pre-Pleistocene fossil mite from the Southern Hemisphere in marine sediments. The specimen is a leg, morphologically assignable to the family Nanhermannidae (Oribatida). The fossil specimen is preserved in a paleopalynological sample from the Río Turbio Formation (Eocene), southwestern Santa Cruz province, Patagonia, Argentina. This finding and the associated claws in palynological samples add an important taxon to the group of non-pollinical palynomorphs with good potential as paleoenvironmental indicators.